Translation Strategy in TikTok Terms: English and Indonesian Version - Adlina, Nuri (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
People communicate through social media using various languages. One social media application that has gained a lot of users during this pandemic time is TikTok. This translation and the popularity of TikTok bring the writer to discuss about the translation of TikTok terms from English to Indonesian. The purposes of this research were to analyze the principle of translation, strategy of translation and the most dominant strategy used by the translator in translating TikTok terms from English to Indonesian. This research used qualitative methodology. The technique of analyzing data in this research used qualitative approach. This study uses the theory of Chesterman of Translation strategy. The writer collected 50 TikTok terms from the app. The terms consist of 18 words, 21 phrases and 11 clauses. The writer found out some principles in terms used in Indonesian version of TikTok app which is translated from the English version: meaning, idiom, and source language influence. From 50 data collected, the writer found 6 kinds of translation strategies and used in translating terms from English version of TikTok app to Indonesian version. The translator employed literal translation strategy in 28 collected data, calque strategy in 10 collected data, loan strategy in 1 collected data, naturalization in 1 collected data, and unit shift in 4 collected data.